MRONJ in breast cancer patients under bone modifying agents for cancer treatment-induced bone loss (CTIBL): a multi-hospital-based case series - Rodolfo Mauceri; Martina Coppini; Massimo Attanasio; Alberto Bedogni; Giordana Bettini; Vittorio Fusco; Amerigo Giudice; Filippo Graziani; Antonia Marcianò; Marco Nisi; Gaetano Isola; Rosalia Maria Leonardi; et al. (BMC, 2023)
Abstract Background Cancer treatment-induced bone loss (CTIBL) is the most common adverse event experienced by patients affected by breast cancer (BC) patients, without bone metastases. Bone modifying agents (BMAs) therapy is prescribed for the prevention of CTIBL, but it exposes patients to the risk of MRONJ. Methods This multicentre hospital-based retrospective study included consecutive non-metastatic BC patients affected by MRONJ related to exposure to low-dose BMAs for CTIBL prevention. Patients' data were retrospectively collected from the clinical charts of seven recruiting Italian centres. Results MRONJ lesions were found in fifteen females (mean age 67.5 years), mainly in the mandible (73.3%). The mean duration of BMAs therapy at MRONJ presentation was 34.9 months. The more frequent BMAs was denosumab (53.3%). Ten patients (66.7%) showed the following local risk factors associated to MRONJ development: periodontal disease (PD) in three cases (20%) and the remaining six (40%) have undergone PD-related tooth extractions. One patient presented an implant presence-triggered MRONJ (6.7%). In five patients (33.3%) no local risk factors were observed. Conclusions This is the first case series that investigated BC patients under BMAs for CTIBL prevention suffering from MRONJ. These patients seem to have similar probabilities of developing MRONJ as osteo-metabolic ones. Breast cancer patients under BMAs for CTIBL prevention need a regular prevention program for MRONJ, since they may develop bone metastases and be treated with higher doses of BMAs, potentially leading to a high-risk of MRONJ.